Analysis Factors Related to Primary Dysmenorrhea in Adolescent Girls at MTS Negeri Surabaya II - Stefani Angel; Ni Ketut Alit; Retnayu Pradanie (Universitas Airlangga, 2016)
Introduction : Dysmenorrhea or menstrual pain is a common problem complained of by the teens that can interfere with daily activities and productivity adolescents. This study was aimed to analyze factors associated with the incidence of primary dysmenorrhea (nutritional status, physical activity and stress) in adolescent girls at MTs Negeri Surabaya II. Methods : This research used is a cross-sectional sample of 49 female students of class VIII. Sampling was done by simple random sampling technique. The independent variable in this study is the nutritional status, physical activity and stress. While the incidence of primary dysmenorrhea is the dependent variable. Data were obtained through a questionnaire and analyzed by using Spearman rank with a significant level of p <0.05. Results : The results of this study found that nutritional status is not associated with the incidence of primary dysmenorrhea (p = 1.00), physical activity associated with the incidence of primary dysmenorrhea (p = 0.003), and stress also has a relationship with the incidence of primary dysmenorrhea (p = 0.001). Discussion: The nutritional status does not increase the risk of incidence of primary dysmenorrhea in adolescents, whereas physical activity and stress can increase the risk of incidence of primary dysmenorrhea in adolescent girls at MTs Negeri Surabaya II.